2018
DOI: 10.1111/jwas.12531
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Four Different Feeding Techniques on the Pond Culture of Pacific White Shrimp, Litopenaeus vannamei

Abstract: The purpose of this study was to examine the effects of four feed‐management techniques on the production of Pacific white shrimp, Litopenaeus vannamei, using a 16‐wk trial performed in 16, 0.1‐ha ponds stocked at 17 shrimp/m2. Four treatments were used for this study: standard feeding protocol (SFP) fed twice daily, a 15% increase to the SFP fed twice daily, timer feeders programmed to feed six times daily following the SFP, and ad libitum using the AQ1 acoustic demand feeding system. Significant increases in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…There are conflicting reports of how many feeding per day improves growth, Robertson, Lawrence, and Castille () found significant improvement from 1 to 2 or 4 feedings per day, Velasco, Lawrence, and Castille () reported increasing above 4 feedings per day did not improve growth. However, Ullman, Rhodes, Hanson, Cline, and Davis () proved growth was improved significantly when fed six times daily compared with two times daily. The speculation is the increased feeding frequency results in higher nutritional value of feed due to the reduction of nutrient leaching.…”
Section: Percent Of the Standard Feeding Protocol Fed To Each Treatmementioning
confidence: 99%
“…There are conflicting reports of how many feeding per day improves growth, Robertson, Lawrence, and Castille () found significant improvement from 1 to 2 or 4 feedings per day, Velasco, Lawrence, and Castille () reported increasing above 4 feedings per day did not improve growth. However, Ullman, Rhodes, Hanson, Cline, and Davis () proved growth was improved significantly when fed six times daily compared with two times daily. The speculation is the increased feeding frequency results in higher nutritional value of feed due to the reduction of nutrient leaching.…”
Section: Percent Of the Standard Feeding Protocol Fed To Each Treatmementioning
confidence: 99%
“…Note that Diet 3 was formulated to be used in both series. In addition, we added another reference, FM-free shrimp diet produced by Zeigler Bros, Inc., as a benchmarking treatment (Diet 8), which has an equivalent formulation and proximate composition as reported by Ullman, Rhodes, Hanson, Cline, and Davis (2017).…”
Section: Experimental Dietsmentioning
confidence: 99%
“…Other work showed that increasing feed allowance does not enhance shrimp performance. In a recent study, Ullman et al (2019) found that increasing feed rations by 15% when feeding twice a day results in no advantage to L. vannamei performance. Shrimp were fed a 375 g kg −1 CP feed, but the amino acid composition was not reported.…”
Section: Discussionmentioning
confidence: 97%